In search of Six Sigma in Portuguese SMEs - Fonseca, Luís Miguel (2017)
This exploratory research aims to study the reasons for the low implementation level of Six Sigma within Portuguese Small and Medium Enterprises. The results suggest that ISO 9001 certification, and Lean Management, are still regarded as enough for company success. The descriptive analysis and the statistical tests performed led to the conclusion that there are no significant differences for the motivations not to implement Six Sigma between small and medium companies. The qualitative research with focus groups highlighted that SMEs aiming for fast improvement results focus more on Lean Management and Kaizen, by using Five S methodology, visual management at shop floor level and basic quality tools. However, there are different views concerning Six Sigma applicability and value for SMEs, suggesting the need for further in-depth research. Within this context, the edition of ISO 9001:2015 International Standard with an increased emphasis on process approach and the achievement of the quality management system objectives is a relevant opportunity for using Six Sigma to streamline processes and enhance customer satisfaction and business results.